Microstructure and texture investigation of chemically deposited copper coatings. (March 2015) - Georgieva, M.; Avdeev, G.; Stoychev, D.; Petrova, M.
Abstract : This work reports electron microscopy and X-ray investigations of the structure and texture of thin copper coatings that were chemically deposited (chem Cu) from trilonic electolytes. The relationships between the structure and texture ofchem Cu, and the structure and texture of electrochemically deposited copper coatings have been established. It has been determined that chemically deposited copper coatings have very fine crystal structure, with areas of coherent scattering that are orders of magnitude smaller than their counterparts in matt copper coatings (matt Cu) that are electrochemically deposited from simple (non-complex) sulphuric-acid electrolyte. Additionally, inchem Cu, the axis of preferred orientation is in the <111> direction, while inmatt Cu it is in the <110> direction. Alternatively, bright copper coatings (bright Cu) (electrodeposited from similar sulphuric acid electrolyte but with brightener additives), which are also characterised with extremely fine crystal structure have mixed <311> plus <110> texture, at a <311> dominant axis of preferable orientation. The values of microhardness of the copper coatings are arranged in the following sequence: HVmattCu chemCu brightCu, opposite to the crystal size ( D ) and the internal stress (rms) in these three types of coatings – D mattCu > D chemCu > D brightCu and rmsmattCu >rmschemCu ≧rmsbrightCu . The data obtained for D and rms are in good agreement with the Hall–Petch rule on HV-grain size relationship.